2013
DOI: 10.1080/01690965.2012.665932
|View full text |Cite
|
Sign up to set email alerts
|

Processing verb-phrase ellipsis in Mandarin Chinese: Evidence against the syntactic account

Abstract: Theories differ as to how people recover the meaning of verb-phrase (VP) ellipsis. According to the syntactic account, people reproduce the syntactic structure of the antecedent during the processing of VP ellipsis. This account thus predicts that the ellipsis site contains syntactic information. Using the structural priming paradigm, we found that, in Mandarin, an ellipsis prime (a double-object or prepositional-object dative antecedent plus a VP ellipsis) was less effective in priming than a full-form prime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
0
22
1
Order By: Relevance
“…Our results also contrast with recent findings that comprehenders do not appear to instantiate syntactic structure associated with VP ellipsis: Cai et al (2013) found that reading a Mandarin DO or PO sentence involving an elided VP did not prime production of DO or PO sentences respectively. This suggests that they do not syntactically represent the elided VP -in other words, that they do not represent its internal structure (i.e., V PP PP or V PP NP).…”
Section: Syntactic Representation Of Missing Elementscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results also contrast with recent findings that comprehenders do not appear to instantiate syntactic structure associated with VP ellipsis: Cai et al (2013) found that reading a Mandarin DO or PO sentence involving an elided VP did not prime production of DO or PO sentences respectively. This suggests that they do not syntactically represent the elided VP -in other words, that they do not represent its internal structure (i.e., V PP PP or V PP NP).…”
Section: Syntactic Representation Of Missing Elementscontrasting
confidence: 99%
“…(Note that even under an alternative analysis in which gei in DO sentences is treated as a co-verb, (1a) and 1bstill involve two distinct syntactic structures.) Observations that Mandarin DO sentences structurally prime DO sentences, and PO sentences structurally prime PO sentences, further confirm that the two constructions have distinct syntactic structures (Cai et al, 2011(Cai et al, , 2013Cai, Pickering, & Branigan, 2012).…”
Section: Structural Priming and The Construction Of Syntactic Represementioning
confidence: 60%
See 1 more Smart Citation
“…Additional evidence that mental representations of syntactic structure can persist after they have been processed come from structural priming studies (see e.g. Bock and Griffin 2000;Branigan et al 2000;Gries 2005;Kaschak 2007) (though see Cai et al 2012 for an opposing argument).…”
Section: Discussionmentioning
confidence: 99%
“…Structural priming has been observed for different constructions and languages (e.g., Cai, Pickering, Yan, & Branigan, 2011; Salamoura & Williams, 2006; Scheepers, 2003; Bernolet, Hartsuiker, & Pickering, 2007), and in natural speech as well as experiments (Gries, 2005; Jaeger & Snider, 2013; Szmrecsanyi, 2005; see Pickering & Ferreira, 2008, for a review). Most relevantly, structural priming has already been used to study well-formed sentences involving missing elements (Cai, Pickering, & Sturt, 2013), as well as the processing of anomalous sentences (Ivanova, Pickering, Branigan, McLean, & Costa, 2012; Slevc & Momma, 2015). …”
Section: Structural Priming From Anomalous Sentencesmentioning
confidence: 99%